Effects of a long-term separation from online gaming on teenagers' gaming habits - Adelhardt, Zinaida; Eberle, Thomas (Proceedings of the 6th European Conference on Social Media, ECSM 2019, 2019)
Teenagers' preoccupation with online video games is a widely discussed topic. The vast majority of research deals with negative effects of "gaming": violence, depression, and diminishing academic performance. Internet gaming disorder (IGD), video game addiction (VGA) or pathological video gaming (PVG)-an addictive tendency towards video gaming affects millions of gamers across the globe. The prevention of potential addictive behaviour and intervention in case of excessive usage is a complicated issue. Our aim was to evaluate adolescents' reaction to the separation from the world of media and its long-term influence on teenagers' video game usage. Each year, 34 fourteen-and fifteen-year-old adolescents sail around the globe for half a year and thus have the opportunity to challenge their abilities in the real world. Smartphone usage and computer gaming are not allowed while sailing, although adolescents may use their devices during some land-stops. We gathered data before the trip (October 2017), after being separated from computers and smartphones for three weeks (November 2017), at the end of the trip (April 2018) and five months after it (September 2018). Research instruments included standardised questionnaires and in-depth interviews. Teenagers, especially boys, were found to play mostly social games and communicate through these games with those whom they already know offline. Results show that during the trip the teenagers' attitudes towards media have significantly changed and this change remained constant five months after the intervention. Video gaming has dropped significantly (d=.0.362). Video gaming was also found to be correlated with positive attitudes towards media and technology and with such media usage patterns as Internet searching and media sharing. While most of the teenagers completely quitted online gaming after the trip, habits of one teenager-who has demonstrated especially addictive behaviour before the trip-stayed unchanged after our intervention: he continued playing online games several hours a day. Implications, further research perspectives and limitations will be presented and discussed.
CRIS-Team Scopus Importer:2019-08-09
Keywords: Attitudes towards media; Excessive gaming; Online video gaming; Social gaming; Teenagers' media usage